Impact of extracorporeal membrane oxygenation on voriconazole plasma concentrations: A retrospective study - Ye, Qinghua; Yu, Xin; Chen, Wenqian; Li, Min; Gu, Sichao; Huang, Linna; Zhan, Qingyuan; Wang, Chen (Frontiers in Pharmacology, 2022)
Aims: We aimed to assess the impact of extracorporeal membrane oxygenation (ECMO) on voriconazole exposure. Methods: Adult critically ill patients with or without ECMO support receiving intravenous voriconazole therapy were included in this retrospective study conducted in a tertiary referral intensive care unit. The first therapeutic drug monitoring (TDM) results of voriconazole in ECMO patients and non-ECMO patients were collected, and the prevalence of subtherapeutic concentrations was analyzed. Multivariate analyses were performed to evaluate the effect of ECMO on voriconazole exposure. Results: A total of 132 patients (including 66 patients with ECMO support) were enrolled and their respective first voriconazole trough concentrations (Cmin) were recorded. The median Cmin of the ECMO group and the non-ECMO group was 1.9 (1.4-4.4) and 4.4 (3.2-6.9) mg/L, respectively (p=0.000), and the proportion of the two groups in subtherapeutic concentrations range (<2mg/L) was 51.5% and 7.6%, respectively (p=0.000). Multiple linear regression analysis of voriconazole Cmin identified that the use of ECMO and coadministration of glucocorticoids were associated with significantly reduced concentrations, while increasing SOFA score and increasing daily dose were associated with significantly increased concentrations. The model accounted for 32.2% of the variability of voriconazole Cmin. Furthermore, binary logistic regression demonstrated that the use of ECMO was an independent risk factor (OR=7.78, p=0.012) for insufficient voriconazole exposure. Conclusion: Our findings showed that, in addition to the known drug interactions, ECMO is a significant covariable affecting voriconazole exposure. In addition, SOFA score was identified as a factor associated with increased voriconazole concentration.